Pengembangan Media Pembelajaran Materi Segi Empat di SMP/MTs Berbasis Budaya Islami dalam Suku Gayo - Fitri, Liana; Ibrahim, Lukman; Duskri, M. (Mathieu : Journal of Mathematics Education and Learning, 2026)
This study aims to describe the process of developing mathematics learning media based on ethnomatics for grade VII at MTsN 1 Aceh Tengah, MTsN 7 Aceh Tengah and SMPN 4 Takengon, namely by using openwork motifs typical of the Gayo tribe, and to determine the response of teachers and students to the development of instructional media. Mathematics based on Islamic culture in the Gayo tribe uses the 4D development model so that it can determine the effectiveness of learning media. Data collection techniques in this study were interviews and questionnaires. Based on the results of research, the teacher's response to the media obtained an average score of 4.61 where x> 3.25 with the criteria "very good". In the trial to students, an average score of 4.46 was obtained where x> 3.25 with the criteria "very good". Based on this assessment, the Islamic culture-based quadrangle mathematics learning media can be used as a complement to teaching materials.